Re/constructing the past: How young people remember the Uruguayan dictatorship - Achugar, Mariana and Fernández, Amparo and Morales, Nicolás (Discourse & Society, 2013)
Investigating how contested periods are remembered by younger generations allows us to better understand the contents that are passed on as well as the discursive processes through which intergenerational transmission occurs. This article explores the intersections of collective and personal memory. We investigate what Uruguayan teenagers know about the dictatorship (1973–1985) and what discourses come into play in shaping these views. The analysis of a group interview, part of an ethnographic project, identifies arguments, representations and evaluations of the period, while exploring intertextual links. The findings show that there are four main arguments used by the youth to explain the dictatorship: reaction to guerrillas, authoritarianism, regional ideological war, and intolerance. The social actors are evaluated in terms of social sanctions with negative evaluations of the guerrilla. Intertextual connections foreground the reception of hegemonic discourses that explain the period in terms of ‘two demons’. What youth know about the past is a situated and socially distributed web of meanings that help them make sense of the past and construct their socio-political identities.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTU3OTI2NTEyNDcxNzU4